Recovery from Choriocarcinoma Syndrome Associated with a Metastatic Extragonadal Germ Cell Tumor Hemorrhage - Koji Komori; Daisuke Takahari; Kenya Kimura; Takashi Kinoshita; Seiji Ito; Tetsuya Abe; Yoshiki Senda; Kazunari Misawa; Yuichi Ito; Norihisa Uemura; Seiji Natsume; Jiro Kawakami; et al. (Case Reports in Gastroenterology, 2016)
A germ cell tumor is the most common form of malignancy in early male life, and can be classified as either seminomatous or nonseminomatous. Choriocarcinoma, comprised of nonseminomatous germ cells, is the most aggressive type of germ cell tumor and characteristically metastasizes to the retroperitoneal lymph nodes and less frequently to the lungs, liver, bone or brain [Shibuya et al., 2009;48: 551–554]. A 56-year-old man was admitted to another hospital complaining of abdominal distension. Symptoms included anorexia, vomiting, and diarrhea. The patient was diagnosed with an extragonadal germ cell tumor and referred to our hospital to receive chemotherapy. The day after admission, the patient’s abdominal distension gradually worsened. An emergency operation revealed venous hemorrhage from the surface of a metastatic extragonadal germ cell tumor between the ligament of Treitz and the inferior mesenteric vein in a horizontal position. Hemostatic treatment was performed with 4-0 proline thread attached to a medicated cotton sponge, rather than using a simple proline thread, and the closure area was manually compressed. Chemotherapy was initiated on postoperative day 10. A metastatic extragonadal germ cell tumor that causes massive hemorrhage and gastrointestinal hemorrhage is very rare, and represents a life-threatening emergency. If the patient’s condition carries a substantial risk of bleeding to death, it may be worthwhile to attempt abdominal operations.